2011
DOI: 10.1159/000322797
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Symptoms of Anxiety and Depression in a Sample of Arab College Students Using the Hopkins Symptom Checklist 25

Abstract: Background: The controversy over the relationship between symptoms of anxiety and depression is an enduring issue. Various models have been proposed to explain this relationship. We explored the following research questions. First, using exploratory factor analysis (EFA), will the symptoms that define anxiety and depression (as in the Hopkins Symptom Checklist 25, HSCL-25) appear together in 1 factor, or are they separable into the hypothesized dimensions of the disorders? Second, using confirmatory factor ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 137 publications
(172 reference statements)
4
30
1
1
Order By: Relevance
“…Although research showed that headaches are usually part of the anxiety scale (e.g. Al-Turkait et al, 2011; Glaesmer et al, 2013) or at least coincide with depression and anxiety (Juang, Wang, Fuh, Lu, & Su, 2000; Zwart et al, 2003), in our non-western refugee groups headache was part of neither the depression nor the anxiety scale. This indicates that among non-western refugee groups headache is not part of depression or anxiety.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Although research showed that headaches are usually part of the anxiety scale (e.g. Al-Turkait et al, 2011; Glaesmer et al, 2013) or at least coincide with depression and anxiety (Juang, Wang, Fuh, Lu, & Su, 2000; Zwart et al, 2003), in our non-western refugee groups headache was part of neither the depression nor the anxiety scale. This indicates that among non-western refugee groups headache is not part of depression or anxiety.…”
Section: Discussioncontrasting
confidence: 54%
“…According to Al-Turkait and colleagues (2011), most scholars found evidence for the 2-factor model and the 3-factor model of the HSCL-25. The 2-factor model comprises symptoms specific to anxiety and symptoms specific to depression, and the 3-factor model additionally distinguishes nonspecific symptoms of general distress which the two disorders share (Al-Turkait et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measure has been adapted and translated for use in conflict settings in Asia [1113], the Middle East [14], Africa [15, 16], and the former Yugoslavia [17, 18]. The HSCL-25 is currently available in a wide range of languages including Arabic [19], Hmong [20], Kiswahili [16], Pashto [14], Farsi, Dari, Bosnian, Somali [9], Vietnamese [21], Swedish [22], Serbo-Croatian, Russian [23], Tibetan [13], Indochinese [24, 25], and Khmer.…”
Section: Introductionmentioning
confidence: 99%
“…Although the difference in the correlations may not be clinically significant, it suggests that there was a comorbidity of depression and anxiety in our sample. This may have two not mutually exclusive explanations: a) The comorbidity of depression and anxiety is evident worldwide (Kessler et al, 2015) and in the Arabic population specifically (Al-Turkait et al, 2011;Belzer and Schneier, 2004;Ohaeri et al, 2010) and b) there is evidence that depression is correlated to anxiety in patients with heart disease (Frasure-Smith et al, 1995;Watkins et al, 2013) and this comorbidity can affect between 21% to 26% of the patients (Doering et al, 2010;Frasure-Smith and Lesperance, 2008). Both explanations support the validity of the A-CDS.…”
mentioning
confidence: 97%